Energetic control of redox-active polymers toward safe organic Bioelectronic materials - Giovannitti,A; Rashid,RB; Thiburce,Q; Paulsen,BD; Cendra,C; Thorley,K; Moia,D; Mefford,JT; Hanifi,D; Weiyuan,D; Moser,M; Salleo,A; et al. (Advanced Materials, 2020)
Avoiding faradaic side reactions during the operation of electrochemical devices is important to enhance the device stability, to achieve low power consumption, and to prevent the formation of reactive sideproducts. This is particularly important for bioelectronic devices, which are designed to operate in biological systems. While redoxactive materials based on conducting and semiconducting polymers represent an exciting class of materials for bioelectronic devices, they are susceptible to electrochemical sidereactions with molecular oxygen during device operation. Here, electrochemical side reactions with molecular oxygen are shown to occur during organic electrochemical transistor (OECT) operation using highperformance, stateoftheart OECT materials. Depending on the choice of the active material, such reactions yield hydrogen peroxide (H2O2), a reactive sideproduct, which may be harmful to the local biological environment and may also accelerate device degradation. A design strategy is reported for the development of redoxactive organic semiconductors based on donor–acceptor copolymers that prevents the formation of H2O2 during device operation. This study elucidates the previously overlooked sidereactions between redoxactive conjugated polymers and molecular oxygen in electrochemical devices for bioelectronics, which is critical for the operation of electrolytegated devices in applicationrelevant environments.